FEATURES OF MODERN TRANSFORMABLE FURNITURE DESIGN - Хоменко, Марія (SWorldJournal, 2025)
The article explores the relevance and innovation of transformable furniture design in modern interior solutions, especially in the context of urbanization and limited living spaces. It examines key design principles such as modularity, combinatorics, an